Insulin and exercise improved muscle function in rats with severe burns and hindlimb unloading. Issue 14 (28th July 2019) - Song, Juquan; Baer, Lisa A.; Threlkeld, Melody R. S.; Geng, Calvin; Wade, Charles E.; Wolf, Steven E.
Abstract: Prior work established that exercise alleviates muscle function loss in a clinically relevant rodent model mimicking the clinical sequelae of severely burned patients. On the basis of these data, we posit that pharmacologic treatment with insulin combined with exercise further mitigates loss of muscle function following severe burn with immobilization. Twenty‐four Sprague–Dawley rats were assessed and trained to complete a climbing exercise. All rats followed a standardized protocol to mimic severe burn patients (40% total body surface area scald burn); all rats were immediately placed into a hindlimb unloading apparatus to simulate bedrest. The rats were then randomly assigned to four treatment groups: saline vehicle injection without exercise (VEH/NEX), insulin (5 U/kg) injection without exercise (INS/NEX), saline vehicle with daily exercise (VEH/EX), and insulin with daily exercise (INS/EX). The animals were assessed for 14 days following injury. The groups were compared for multiple variables. Isometric tetanic (Po) and twitch (Pt) forces were significantly elevated in the plantaris and soleus muscles of the INS/EX rats ( P < 0.05). Genomic analysis revealed mechanistic causes with specific candidate changes. Molecular analysis of INS/EX rats revealed Akt phosphorylated by PDPK1 was increased with this treatment, and it further activated downstream signals mTOR, eEF2, and GSK3‐ β ( P < 0.05). Furthermore, muscle RING‐finger protein‐1 (MuRF‐1), an E3 ubiquitin ligase, was reduced in the INS/EX group ( P < 0.05). Insulin and resistance exercise have a positive combined effect on the muscle function recovery in this clinically relevant rodent model of severe burn. Both treatments altered signaling pathways of increasing protein synthesis and decreasing protein degradation. Abstract : Insulin and resistance exercise have a positive combined effect on the muscle function recovery in burn and hindlimb unloaded rats. Both treatments altered signal pathways of regulating protein metabolism in transcriptional and protein levels.